2019
DOI: 10.1111/ggi.13627
|View full text |Cite
|
Sign up to set email alerts
|

Association between sarcopenia and sleep disorder in older patients with diabetes

Abstract: Aim In the present study, we aimed to examine the association between sarcopenia and sleep disorder in older patients with diabetes using the Japanese version of SARC‐F (SARC‐F‐J). Methods Outpatients with diabetes (aged ≥65 years) at the Ise Red Cross Hospital were included in the present study. We used the Japanese version of the Pittsburgh Sleep Quality Index, which is a self‐administered questionnaire, to measure sleep disorder. To evaluate sarcopenia, we used SARC‐F‐J, a self‐administered questionnaire, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…On the other hand, the grouped odds ratios (OR) and their IC95% were also calculated following a model of "quality effects" [31,33] to analyze the association between those who sleep well (control) and those who sleep poorly (effect). In addition, OR and sleep category analysis were estimated, excluding studies that did not report participants' total hours of sleep and only showed sleep quality [19,34]. Heterogeneity between studies was conducted using the I 2 statistic, and the variation between studies was calculated using the tau 2 statistic (τ 2 ) [35].…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the grouped odds ratios (OR) and their IC95% were also calculated following a model of "quality effects" [31,33] to analyze the association between those who sleep well (control) and those who sleep poorly (effect). In addition, OR and sleep category analysis were estimated, excluding studies that did not report participants' total hours of sleep and only showed sleep quality [19,34]. Heterogeneity between studies was conducted using the I 2 statistic, and the variation between studies was calculated using the tau 2 statistic (τ 2 ) [35].…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…After the removal of duplicated articles from the different databases, 361 titles and abstracts, as well as 106 articles, were reviewed, and 255 were removed. Finally, statistical analysis was performed on a total of 6 studies [19,34,[36][37][38][39] (5 were performed in Asia and only 1 in Europe; Figure 1), with a mean age of 68.7 years (range = 44-80 years). Table 1 shows the descriptive characteristics of the studies included in our analysis.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations